Contributions of Ashraf Ali Thanwi to mental disease treatment - Isqeel, Abdullateef Ayodele; Daoud, Jamal Ibrahim (IIUM Press, 2011)
The methodology adopted in this chapter is library and internet based. The data used were collected from dependable sources. The understanding ofAshraf Ali Thanwi work in psychology was investigated and the scope is to examine and explain Islamic psychology as viewed and practiced for treatment of maladjusted person by Asharf Ali Thanwis. The significance of this chapter is the usefulness of Thanwi's methodology in healing through Islamic perspective. Psychology is the science of the mind and behavior. The word "psychology" comes from the Greek word psyche meaning "breathe, spirit, soul", and the Greek word logia meaning the study of something. According to Medilexicon's Medical Dictionary, psychology is "The profession (clinical psychology), scholarly discipline (academic psychology), and science (research psychology) concerned with the behavior of humans and animals, and related mental and physiologic processes" (http://www.medilexicon.com!medicaldictionary.php).